Combined Charge Carrier Transport and Photoelectrochemical Characterization of BiVO4 Single Crystals: Intrinsic Behavior of a Complex Metal Oxide - Rettie, Alexander J. E; Lee, Heung Chan; Marshall, Luke G; Lin, Jung-Fu; Capan, Cigdem; Lindemuth, Jeffrey; McCloy, John S; Zhou, Jianshi; Bard, Allen J; Mullins, C. Buddie (Journal of the American Chemical Society, 2013)
Bismuth vanadate (BiVO4) is a promising photoelectrode material for the oxidation of water, but fundamental studies of this material are lacking. To address this, we report electrical and photoelectrochemical (PEC) properties of BiVO4 single crystals (undoped, 0.6% Mo, and 0.3% W:BiVO4) grown using the floating zone technique. We demonstrate that a small polaron hopping conduction mechanism dominates from 250 to 400 K, undergoing a transition to a variable-range hopping mechanism at lower temperatures. An anisotropy ratio of ∼3 was observed along the c axis, attributed to the layered structure of BiVO4. Measurements of the ac field Hall effect yielded an electron mobility of ∼0.2 cm2 V–1 s–1 for Mo and W:BiVO4 at 300 K. By application of the Gärtner model, a hole diffusion length of ∼100 nm was estimated. As a result of low carrier mobility, attempts to measure the dc Hall effect were unsuccessful. Analyses of the Raman spectra showed that Mo and W substituted for V and acted as donor impurities. Mott–Schottky analysis of electrodes with the (001) face exposed yielded a flat band potential of 0.03–0.08 V versus the reversible H2 electrode, while incident photon conversion efficiency tests showed that the dark coloration of the doped single crystals did not result in additional photocurrent. Comparison of these intrinsic properties to those of other metal oxides for PEC applications gives valuable insight into this material as a photoanode.